Potential Role of Gut Microbiota in Induction and Regulation of Innate Immune Memory - Negi, Shikha; Das, Deepjyoti Kumar; Pahari, Susanta; Nadeem, Sajid; Agrewala, Javed N. (Frontiers in Immunology, 2019)
The gut microbiota significantly regulates the development and function of innate and adaptive immune system. The attribute of immunological memory has long been linked only with adaptive immunity. Recent evidence indicate that memory is also present in the innate immune cells such as monocytes/macrophages, and natural killer cells. These cells exhibit pattern recognition receptors (PRRs) that recognize microbe- or pathogen-associated molecular patterns (MAMPs or PAMPs) expressed by the microbes. Interaction between PRR and MAMP is quite crucial since it triggers the sequence of signaling events and epigenetic rewiring that play a cardinal role in modulating not only the activation and function of the innate cells but as well as imparts a sense of memory response. We discuss here how gut microbiota can influence the generation of innate memory and functional reprogramming of bone marrow progenitors that helps in protection against infections. This article will broaden our current perspective of association between the gut microbiome and innate memory. In future, this knowledge may pave avenues for development and designing of novel immunotherapies and vaccination strategies.